Resource Curse Impacts in Southern Africa: A Systematic Literature Review of Non-Renewable Resources - Shelton Chinorumba (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This review synthesizes research on the resource curse in Southern Africa, focusing on non-renewable resources to address the paradox of abundant mineral wealth coinciding with economic stagnation, governance challenges, and environmental degradation. The review aimed to evaluate economic impacts, institutional quality, environmental and social risks, foreign direct investment dynamics, and policy effectiveness in the region. A systematic analysis of empirical, theoretical, and policy studies from Southern African countries and the SADC region was conducted, emphasizing quantitative econometric methods and comparative case studies. Findings reveal that institutional quality critically mediates resource wealth outcomes, with strong governance enabling economic growth and diversification while weak institutions exacerbate rent-seeking and socio-environmental harms. Non-renewable resource dependence often correlates with slower growth and environmental degradation, though exceptions exist where effective management fosters human development. Foreign direct investment can mitigate or amplify resource curse effects depending on governance and integration, while policy frameworks and regional cooperation remain essential yet under-evaluated for sustainable resource management. These findings converge to underscore the multifaceted nature of the resource curse, highlighting institutional reforms and integrated policies as pivotal for transforming resource wealth into sustainable development. The review informs future research and policy by delineating critical governance and economic factors shaping resource outcomes in Southern Africa.